An Improved Detection and Diagnosis Methods for Breast Tumor Detection System using IEMD Transform-based CNN Architecture - Nagalakshmi, K.; Suriya, S.; Umadevi, V. (Journal of Information Systems Research and Practice, 2024)
Mammogram is used to screen the tumor pixels in the breast portion of the human body. This paper develops a methodology for detecting and diagnosing the tumor regions in mammogram images using deep learning algorithm. The methodology consists of data augmentation, transform, and Convolutional Neural Networks (CNN) classifier with segmentation process for detecting the malignant mammogram image from the benign mammogram image. Then, the malignant mammogram image is analyzed for its severity levels using CNN classifier. The proposed system diagnosed the malignant case mammogram images into either Early or Advance using the developed CNN architecture. The simulation results of the proposed methods are compared with respect to other similar studies in this field.